Shaken Baby Syndrome Association of Convulsion with Child Abuse During Infancy Period a Presentation of Three Forensic Cases - Tüzün, Birgül; Üçsel, Raif; Alkan, Nevzat; Çıtak, Agop; Fincancı, Şebnem Korur (The Bulletin of Legal Medicine, 2000)
The possibility of manifest traumatic changes is rare for physical abuse during infancy. Cases are brought to emergency-intensive care units because of clinical findings observed in various diseases, which are unique to this age and which are mostly reported to come out immediately. In this study, a male and two female infants who were taken to the child emergency-intensive care unit of Istanbul Medical Faculty of University of Istanbul with a clinical finding such as convulsion are presented in order to document the way they were referred to the department, and to stress the importance of the stand point of forensic medicine in the process of orienting towards the proper diagnosis. In all of the three cases, a recent fall history, subdural hematoma identified in brain tomography, massive retinal hemorrhage identified as a result of the examination of the rear part of the eye were present. A diagnostic of child abuse was determined according to the medical history. In conclusion, for a proper diagnosis of physical abuse without delay, considering them as forensic cases, and documenting identified traumatic changes as forensic reports and reporting them to judicial offices, thus the work in coordination with Forensic Medicine Departments is extremely important.Keywords: : Child abuse, subdural hematoma, shaken baby syndrome.
Keywords: child abuse; subdural hematoma; shaken baby syndrome